Routledge handbook of religion and ecology - Grim, John; Jenkins, Willis; Tucker, Mary Evelyn (Routledge international handbooks, 2017)
pt. 1. Introducing religion and ecology -- pt. 2. Global traditions -- pt. 3. Indigenous cosmovisions -- pt. 4. Regional landscapes -- pt. 5. Nature spiritualities -- pt. 6. Planetary challenges -- pt. 7. Disciplinary intersections.